Differentiating Cannabis Products: Drugs, Food, and Supplements - Salehi, Arash; Puchalski, Keely; Shokoohinia, Yalda; Zolfaghari, Behzad; Asgary, Sedigheh (Frontiers in Pharmacology, 2022)
"Hemp" refers to non-intoxicating, low delta-9 tetrahydrocannabinol (Δ9-THC) cultivars of Cannabis sativa L. "Marijuana" refers to cultivars with high levels of Δ9-THC, the primary psychoactive cannabinoid found in the plant and a federally controlled substance used for both recreational and therapeutic purposes. Although marijuana and hemp belong to the same genus and species, they differ in terms of chemical and genetic composition, production practices, product uses, and regulatory status. Hemp seed and hemp seed oil have been shown to have valuable nutritional capacity. Cannabidiol (CBD), a non-intoxicating phytocannabinoid with a wide therapeutic index and acceptable side effect profile, has demonstrated high medicinal potential in some conditions. Several countries and states have facilitated the use of THC-dominant medical cannabis for certain conditions, while other countries continue to ban all forms of cannabis regardless of cannabinoid profile or low psychoactive potential. Today, differentiating between hemp and marijuana in the laboratory is no longer a difficult process. Certain thin layer chromatography (TLC) methods can rapidly screen for cannabinoids, and several gas and liquid chromatography techniques have been developed for precise quantification of phytocannabinoids in plant extracts and biologic samples. Geographic regulations and testing guidelines for cannabis continue to evolve. As they are improved and clarified, we can better employ the appropriate applications of this uniquely versatile plant from an informed scientific perspective.